Avaliação dos parâmetros fermentativos relacionados ao perfil de aminoácidos e vitaminas em diferentes variedades de cana-de-açúcar utilizando Saccharomyces cerevisiae PE-2 - Santos, Tatiane Oliveira dos (2024)
The sugarcane culture is one of Brazil's main economic activities, being the predominant raw material in bioethanol production, an alternative to fossil fuels for decarbonizing the transportation sector. Although the production process is well elucidated, there are numerous possibilities for optimizing ethanol production. Since almost all ethanol production is done through the fermentation of sugarcane, and yeast have specific nutritional requirements, knowledge of the chemical composition of sugarcane juice is of great importance for achieving the highest efficiency in converting sugars into ethanol. Therefore, this study aimed to characterize the wort obtained from five sugarcane cultivars in terms of sugars, free amino acids, and vitamins. Fermentation assays were performed with the worts of each cultivar separately. Fermentation started with 130 g.L- 1 of total sugars (sucrose, glucose, and fructose) and lasted 72 hours, using the Saccharomyces cerevisiae PE-2 strain. The chemical composition of the worts was determined for sugars, amino acids, and vitamins, before and after fermentation by HPLC. Fermentative parameters such as substrate to biomass conversion factor (Yx/s), substrate to product conversion factor (Yp/s), productivity (ϕ), and fermentation efficiency (η) were calculated and subjected to one-way analysis of variance (ANOVA) and Tukey test, both at a statistical significance level of 5%. All cultivars showed good efficiency in alcoholic fermentation: 86.6% (RB867515), 88.2% (RB044108), 92.6% (RB988082), 93.5% (RB034045), and 97.4% (RB074067). Statistical differences were observed among most fermentative parameters, with emphasis on cultivar RB074067 with higher ethanol production and lower production of secondary metabolites. The quantified amino acids (Ala, Arg, Gli, Glu, Met, Tre, and Val) showed concentration variations among cultivars, as did B-complex vitamins (B1, B3, B5, B6, B7, and PABA). Total consumption of most amino acids and vitamin biosynthesis by yeast during fermentation were observed. The fermentation results highlight cultivar RB074067 as a promising variety for achieving increased industrial alcoholic fermentation efficiency with S. cerevisiae PE-2 without additional costs for nutrient supplementation to correct the wort's chemical composition.